Sensory materials Montessori in the development of the notion of seriation in infants of five years - Navarro Orosco, Lynda Milagros (2018)
The objective of the present investigation was to determine the influence of the sensory materials Montessori in the development of the notion of seriation in infants of five years of an educational institution of Comas, 2016; Experimental design of quasi-experimental type, of longitudinal cut, with a population of 50 infants, the information was obtained by means of the individualized administration of a valuation scale with Likert-type responses, for the analysis of data the statistical program SPSS version 22 was used From the results obtained it was found that the Montessori materials favor the development of the notion of seriation in infants of five years.